2020
DOI: 10.1093/jaoacint/qsaa062
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Extraction Combined with Ultra-High-Performance Liquid Chromatography-Tandem Mass Spectrometry for the Determination of 5 Trace Nitro-Polycyclic Aromatic Hydrocarbons in Barbecued Foods

Abstract: Background Nitrated polycyclic aromatic hydrocarbons (nitro-PAHs) are the derivatives of polycyclic aromatic hydrocarbon which are direct mutagens and carcinogens to human. Nitro-PAHs can be produced in the process of food barbecuing/grilling. At present, there are few studies for the determination of nitro-PAHs in food. Objective To assess the effect of barbecued food to human health, we have established a method for the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…In comparison to our results, 2NFlu and 3NFla were not detected, for 2NFlu in twenty meat and fish samples [ 44 ] and for 3NFla in 11 barbecued samples [ 42 ] and smoked sausages [ 45 ]. Our method did not detect any di-nitro pyrenes (DNPyrs) in samples, which was conversely reported in eight of eleven barbecued foods in a concentration range of 3.2–13 µg/kg (1,8DNPyr, [ 42 ]).…”
Section: Resultscontrasting
confidence: 91%
See 3 more Smart Citations
“…In comparison to our results, 2NFlu and 3NFla were not detected, for 2NFlu in twenty meat and fish samples [ 44 ] and for 3NFla in 11 barbecued samples [ 42 ] and smoked sausages [ 45 ]. Our method did not detect any di-nitro pyrenes (DNPyrs) in samples, which was conversely reported in eight of eleven barbecued foods in a concentration range of 3.2–13 µg/kg (1,8DNPyr, [ 42 ]).…”
Section: Resultscontrasting
confidence: 91%
“…These reported mean concentrations were similar to our result ( Table 3 ). Conversely to us, the 1NPyr has also been commonly detected [ 10 , 11 , 23 , 42 , 45 ]. In comparison to our results, 2NFlu and 3NFla were not detected, for 2NFlu in twenty meat and fish samples [ 44 ] and for 3NFla in 11 barbecued samples [ 42 ] and smoked sausages [ 45 ].…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…No differences in the PANH contents were observed between the raw and fried meat. Qu et al, (2020) compared formation of various nitrated polycyclic aromatic hydrocarbons (nitro-PAHs) in charcoal-grilled and fried food (Qu et al, 2020). In general, it was observed that the concentrations of the nitro-PAHs 1-Nitronaphthalene 1,8-Dinitropyrene and 1-Nitropyrene were higher in grilled food with a concentration range of approximately 1-12 ng/g.…”
Section: Polycyclic Aromatic Hydrocarbon (Pah)-analoguesmentioning
confidence: 99%